Analysis of the Local Wisdom and Role of Women Weavers in Samarinda - Norhidayat Norhidayat (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2022)
Analysis of the Role Women Weavers and Local Wisdom Values ​​ of Tepian Mahakam (Samarinda City) Society in Use of Samarinda style of Woven Fabrics. This study aims to analyze the background of Bugis tribe entry in Samarinda, in addition to this research will explain or analyze the values ​​of local wisdom of the people of the City of Tepian (Samarinda) which is illustrated in the sarong fabric of Samarinda sarong and also look in detail at the role of traditional women weavers and the values ​​of the Samarinda woven motifs. The type of research conducted is qualitative research. This study aims to analyze the values ​​of local wisdom of the people of the City of Tepian(Samarinda) which is illustrated in the sarong of Samarinda. Data collection techniques used are techniques that are usually used in qualitative research methodology which consists of (observation, interview, documentation and library research), source criticism. In addition, interview guides are also used as an instrument to facilitate the collection of data in the form of an explanation of the respondents interviewed and considered competent in the field.